Digital photographer's handbook - Ang, Tom (2020)
This manual outlines key photography techniques and includes a series of projects designed to develop and refine skills.
Core skills -- Photography projects -- Image development -- Showing and sharing -- Buying guide -- Going further.
Includes index.
Keywords: Photography -- Digital techniques; Digital cameras; PHOTOGRAPHY / Individual Photographers; PHOTOGRAPHY / Techniques / Digital; Digital cameras; Photography -- Digital techniques; Handbooks and manuals; Handbooks and manuals